Prosedur Peminjaman dan Elemen Sosiobudaya dalam Terjemahan Rihlat Ibn Battutah Borrowing and the Sociocultural Elements in the Translation of Rihlat Ibn Battutah - Idris Mansor (Kajian Malaysia, 2015)
Socio-cultural factors are the vital elements that normally affect a translation process. This factor's influence is often reflected in the selection of particular translation procedures and strategies. A previous study that has been carried out discovered that "borrowing" is one of the most dominant procedures used by the translators in the translation of certain cultural elements in Rihlat Ibn Battutah into Malay. As such, through "observation and explanation" and with the support of the interview approach, this study is carried out to identify the socio-cultural influences involved in the selection of the main borrowing procedures as the main approach in translating the cultural elements. The results of the study reveal that besides the lack of single equivalence in the target culture, some other external factors also contributed to the selection of "borrowing" as one of the most important procedures in the above translation. Faktor sosiobudaya merupakan antara elemen penting yang kerapkali mempengaruhi proses penterjemahan. Pengaruh faktor ini seringkali dapat dilihat melalui pemilihan prosedur dan strategi tertentu yang digunakan oleh penterjemah. Kajian lepas yang dijalankan mendapati "peminjaman" merupakan antara prosedur utama yang digunakan oleh penterjemah dalam menterjemah beberapa elemen budaya yang terpilih dalam teks Rihlat Ibn Battutah kepada bahasa Melayu. Untuk itu, melalui kaedah "pemerhatian dan penerangan" dan disokong oleh pendekatan temu bual, kajian ini dijalankan bagi mengenal pasti pengaruh sosiobudaya yang terlibat dalam pemilihan prosedur peminjaman sebagai pendekatan utama dalam menterjemahkan elemen-elemen budaya tersebut. Hasil kajian mendapati bahawa selain ketiadaan padanan satu lawan satu bagi data teks sumber yang dipilih, pengaruh faktor-faktor luaran juga terlibat dalam pemilihan peminjaman sebagai antara prosedur penting dalam terjemahan tersebut.